HANGING BY EXCESS: HISTORY, ETHICS AND IDENTITY IN THE NOVEL COLOMBINA DESCUBIERTA BY ALICIA FREILICH (Andamios, Revista de Investigación Social, 2008)
In the 1990s, a significant group of Venezuelan writers has carried out in its fiction a dialogue about the major events of national History. From this dissident group comes the author Alicia Freilich, who in her novel Colombina descubierta (1991), transcends the concept of reproduction of history as a set of identities and resorts to the destabilization of speech, of artefacts of memory and of subjectivity in the most traditional sense of the term. She thus proposes the existence of an ethical identity based on core emotional bonds, and on the individual’s proteic ability.
Keywords: Ethical identity; antihistory; Alicia Freilich; intimacy; subjectivity